Small airway loss in the physiologically ageing lung: a cross-sectional study in unused donor lungs. Issue 2 (February 2021) - Verleden, Stijn E; Kirby, Miranda; Everaerts, Stephanie; Vanstapel, Arno; McDonough, John E; Verbeken, Erik K; Braubach, Peter; Boone, Matthieu N; Aslam, Danesh; Verschakelen, Johny; Ceulemans, Laurens J; Neyrinck, Arne P; et al.
Summary: Background: Physiological lung ageing is associated with a gradual decline in dynamic lung volumes and a progressive increase in residual volume due to diminished elastic recoil of the lung, loss of alveolar tissue, and lower chest wall compliance. However, the effects of ageing on the small airways (ie, airways <2·0 mm in diameter) remain largely unknown. By using a combination of ex-vivo conventional CT (resolution 1 mm), whole lung micro-CT (resolution 150 μm), and micro-CT of extracted cores (resolution 10 μm), we aimed to provide a multiresolution assessment of the small airways in lung ageing in a large cohort of never smokers. Methods: For this cross-sectional study, we included donor lungs collected from 32 deceased never-smoking donors (age range 16–83 years). Ex-vivo CT and whole lung high-resolution CT (micro-CT) were used to determine total airway numbers, stratified by airway diameter. Micro-CT was used to assess the number, length, and diameter of terminal bronchioles (ie, the last generation of conducting airways); mean linear intercept; and surface density in four lung tissue cores from each lung, extracted using a uniform sampling approach. Regression β coefficients are calculated using linear regression and polynomial models. Findings: Ex-vivo CT analysis showed an age-dependent decrease in the number of airways of diameter 2·0 mm to less than 2·5 mm (β coefficient per decade −0·119, 95% CI −0·193 to −0·045; R 2 =0·29) and especially in airways smaller than 2·0 mm in diameter (−0·158, −0·233 to −0·084; R 2 =0·47), between 30 and 80 years of age, but not of the larger (≥2·5 mm) diameter airways (−0·00781, −0·04409 to 0·02848; R 2 =0·0007). In micro-CT analysis of small airways, the total number of terminal bronchioles per lung increased until the age of 30 years, after which an almost linear decline in the number of terminal bronchioles was observed (β coefficient per decade −2035, 95% CI −2818 to −1252; R 2 =0·55), accompanied by a non-significant increase in alveolar airspace size (6·44, −0·57 to 13·45, R 2 =0·10). Moreover, this decrease in terminal bronchioles was associated with the age-related decline of pulmonary function predicted by healthy reference values. Interpretation: Loss of terminal bronchioles is an important structural component of age-related decline in pulmonary function of healthy, non-smoking individuals. Funding: Research Foundation—Flanders, KU Leuven, Parker B Francis Foundation, UGent, Canadian Institutes for Health.